FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PERUSAHAAN NON KEUANGAN DI INDONESIA - JONINHO ARIMA RAMADHAN; DEASY ARIYANTI RAHAYUNINGSIH (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this study is to examine the factors that influence firm value in Indonesia. Those factors are leverage policy, liquidity, profitability, firm size, investment policy, dividend policy, managerial ownership, and company growth. The population are non-financial companies listed in Indonesia from the period of 2014 to 2016. This study used 56 samples and samples selection procedure used purposive sampling. This research uses multiple regression analysis method. The result of this study shows that leverage policy, liquidity, profitability, investment policy, managerial ownership has influence toward firm value. Another independent variables such as firm size, dividend policy, company growth has no influence toward firm value.